Peculiarities of the anthroponomastic form of address in Korean - Khan, N (Journal of Oriental Studies, 2016)
The article deals with the peculiarities of the anthroponomastic form of the address in the Korean language, the origin of surnames and the features of the choice of a name. Since personal names are not applied as the address in the Korean language and its functioning is traditionally limited, the aim of the article is to reveal national and specific peculiarities of the anthroponomy.